ISSUES OF ATTRACTING INVESTMENTS IN HUMAN CAPITAL - Zayniddin Aloviddin Zayniddin ugli (Journals Park Publishing, 2025)
The article examines the concept of human capital, the role and importance of attracting investment in human capital, and provides conclusions and recommendations based on international experience, emphasizing that human capital is one of the main factors of economic growth and increasing the competitiveness of the economy in economic development.
Keywords: Human capital, innovation, globalization, competence, electronics, subsidy, green economy, motivation.